Bioconversion of food waste into compost using rotary drum composter for agricultural utilization - Hrishikesh Shivam; Mulbah Rufus Flomo; Dayanand Sharma; Tushar Bansal; Pooja Jha (International Journal of Recycling of Organic Waste in Agriculture, 2025)
Purpose: The goal of this research was to create a higher-quality compost produced by mixing sawdust with food waste and dry leaves in four different trials in a rotary drum composting unit.